2012
DOI: 10.2169/internalmedicine.51.6483
|View full text |Cite
|
Sign up to set email alerts
|

Differential Association between HLA and Diffuse Panbronchiolitis in Northern and Southern Chinese

Abstract: HLA-B54 and HLA-A11 were positively associated with DPB in Northern and Southern Chinese, respectively. Population substructure may impact the genetic predisposition of DPB in China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Studies have shown that DPB is closely related to HLA-A11 and HLA-B54. 2 However, the two sisters with DPB were both negative for HLA-A11 and HLA-B54, but positive for HLA-A24 and HLA-B13. Interestingly, their father and younger brother were positive for HLA-A11, but there was no evidence of diffuse panbronchiolitis.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Studies have shown that DPB is closely related to HLA-A11 and HLA-B54. 2 However, the two sisters with DPB were both negative for HLA-A11 and HLA-B54, but positive for HLA-A24 and HLA-B13. Interestingly, their father and younger brother were positive for HLA-A11, but there was no evidence of diffuse panbronchiolitis.…”
Section: Discussionmentioning
confidence: 96%
“…1 It is a rare complex genetic disease that mainly affects East Asians and is strongly associated with the class I human leukocyte antigen (HLA)-B54 in Japanese and HLA-A11 in Koreans. 2 This uneven distribution is suspected to be highly associated with genetic predisposition located between HLA-A and HLA-B loci. More than 80% of the patients have chronic sinusitis, which usually precedes the lower respiratory tract symptoms by years.…”
Section: Introductionmentioning
confidence: 99%
“…Infections and immune conditions associated with HLA-A11 expression have been investigated; these include familial otosclerosis, pulmonary tuberculosis, leprosy, cytomegalovirus infection with epilepsy, osteosarcoma, antidepressant-induced hepatitis, steroid-responsive nephrotic syndrome, and diffuse panbronchiolitis. [19][20][21][22][23][24][25][26] It has been proposed that immunologic responses are initiated under certain conditions by general or unique HLA determinants in susceptible A11 carriers. 27 The presence of certain HLA antigens renders patients susceptible to MD; ethnic differences in HLA-associated genes may partially explain the variations in MD incidence among populations.…”
Section: Discussionmentioning
confidence: 99%
“…For example, HLA-B54 and HLA-A11 were positively associated with diffuse panbronchiolitis in Northern and Southern Chinese, respectively. 26 Therefore, it is reasonable that DRB1*09 should be protective in a Beijing Han population (Northern Chinese) with MD but that A*11 should increase MD susceptibility in a Taiwanese population (East-Southern Chinese).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to Japanese population, this study with Koreans identified HLA-DR*13 as a protective genetic marker against DPB. The rarity of the disease and the subsequent studies low sample number adds great difficulties to obtain conclusive results in others than Japanese population, but positive association with DPB were confirmed in Chinese patients for HLA-A*11 and -B*54 [124,125,126] .…”
Section: Idiopathic Bronchiectasismentioning
confidence: 99%